Smart Governance, Weak Implementation? Evaluating Digital Civil Servants Competence in the Age of E-Government - Frans Tory Damara Pradipta (Jurnal MSDA (Manajemen Sumber Daya Aparatur), 2026)
Digital transformation in government through the implementation of e-government has become an essential component in achieving smart governance. The success of digital policy implementation depends not only on the availability of technological infrastructure but also on the digital competencies of civil servants as the primary actors responsible for executing public policies. This study aims to evaluate the digital competencies of civil servants and identify factors influencing the effectiveness of smart governance implementation in the e-government era. The research employed a qualitative approach using a literature review method based on scientific articles, government reports, and other relevant publications discussing digital competence, e-government, and smart governance. The findings indicate a significant gap between the advancement of digital governance policies and the actual digital capacities of civil servants in bureaucratic practices. Digital competencies remain unevenly distributed, technology utilization is largely administrative in nature, and competency development programs have not fully addressed the demands of digital transformation. Furthermore, conventional work cultures and limited adaptability to technological change continue to hinder the effectiveness of digital governance initiatives. The study highlights that digital competence is a critical factor in supporting the successful implementation of smart governance and digital bureaucratic transformation in Indonesia.